A Novel Piezoelectric-Electromagnetic Vibration Energy Harvesting Device With Real-Time Adjustable Resonant Frequency - Weijia Xiu; Yanchun Yao; Liang Li; Xibin Li; Jida Wu (IEEE Access)
To address the problems of the piezoelectric-electromagnetic vibration energy harvesting device, which exists in the collection frequency band, is not adjustable, and does not fully utilize the magnetic potential energy, this paper designs a piezoelectric-electromagnetic vibration energy harvesting device which adjusts the resonance frequency by changing the magnetic distance and introduces the bending piezoelectric transducer to make full use of the magnetic potential energy. The magnetic force between magnets is derived from the magnetic dipole model, and the relationship between the voltage and power of each power generation part is described theoretically. In the capacity characterization test of the vibration energy harvesting device, the influence of the laws of load resistance, excitation acceleration, magnetic distance, and excitation frequency on the output voltage and power was investigated. When the excitation acceleration is 0.5g and 2g, the output power is 1.68 mW and 9.1 mW, respectively; when the magnetic moment is 48 mm and 68 mm, the vibratory energy recovery device reaches the peak power at 18 Hz and 12.4 Hz, respectively, and when the magnetic moment is 58 mm, the double-peak power appears at 13.8 Hz and 14.4 Hz. The results show that the adjustment of the magnetic pitch can change the magnitude of the magnetic force between the permanent magnets, and the nonlinear magnetic force can change the device’s resonance frequency and frequency band, which significantly enhances the device’s energy the efficiency of energy collection of the device is significantly improved; the bending piezoelectric transducer improves the utilization of magnetic potential energy and enhances energy collection.